The Effect of Bima Bay Water Quality Conditions on the Sea Snot Phenomenon - Makbul Hidayat; Feny Arafah; Asryadin; Masrurotul Ajiza (Institut Teknologi Sepuluh Nopember, 2026)
Sea Snot is phenomenon that occurs in waters characterized by the collection of mucus or sludge on the surface of the sea which is an accumulation of various types of microorganisms such as phytoplankton and bacteria. The first occurrence in Indonesia was reported in Bima Bay on April 25, 2022. This study aims to assess the water quality of Bima Bay using Sea Surface Temperature (SST), Dissolved Oxygen (DO), and Salinity parameters derived from Landsat satellite imagery and validated through field surveys. Based on the results of determining the quality status of Bima Bay waters, shows that there is a change in quality status at each point from 2022 to 2023. From a total of 50 sample points, it shows that there are 44% of points that still have lightly polluted status and from good to lightly polluted status there are 18%. This shows that there is still lightly pollution of 62% in the waters of Bima Bay after one year of the sea snot phenomenon. The condition of Bima Bay's waters does not have the status of being moderately or heavily polluted. These findings highlight the need for increased environmental awareness among local communities to prevent further degradation of Bima Bay’s waters.